LITERACY ISLAMIC EDUCATION MANAGEMENT ISLAMIC BOARDING SCHOOL - Musa Musa (International Journal of Southeast Asia, 2021)
The importance of knowledge and understanding of Islamic education management in Islamic boarding schools, especially for leaders of educational institutions. Leaders should have compiled an annual program related to teachers, of course, namely: Teaching programs such as, among others, the need for teachers in connection with transfers and others, division of teaching tasks, procurement of textbooks, teaching tools and visual aids, procurement and development laboratory, library procurement and development, learning outcomes assessment system, extracurricular activities and others. Student programs such as the terms and procedures for new student admissions, student grouping, class division, guidance and counseling, health services and others. Staffing such as acceptance and placement of teachers, division of duties of teachers and supervisors, welfare of teachers and employees, transfers and promotions and so on. Finance includes procurement and financial management for various planned activities, both money from the government and foundations. Equipment includes renovation of physical infrastructure and addition of workspaces, study rooms and so on. Many factors must be considered in planning such as economic, social, political and cultural factors, laws and regulations, the development of science and technology and the existence of other Islamic boarding schools. Planning is always related to the future which is always changing rapidly, without planning educational institutions, including Islamic boarding schools, will lose opportunities and cannot answer questions about what will be achieved, how to achieve it. Therefore, planning must be made so that humans can be focused on the goals to be achieved.